1988
DOI: 10.1111/j.1095-8649.1988.tb05397.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of inflammatory neutrophils induced by bacterial endotoxin in the blood of eels, Anguilla australis

Abstract: Peripheral blood neutrophils were studied in eels injected with phosphate bulkred saline, bacterial lipopolysaccharidc (LPS), carrageenan (CAR). LPS and CAR together (CAR/LPS(T)), CAR and LPS 4 days later (CAR/LPS(S)), zymosan and latex beads. All stimuli caused a left shift toward ncutrophil immaturity but LPS-elicited neutrophils. particularly in CAR/LPS stimulated eels, were often extremely bdsophik. enlarged, vacuolated and had a large nucleus with poorly differentiated nuclear chromatin. These intensely b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…Some changes were noticed in the morphology of leukocytes of O. niloticus during the course of the infection process. After the 4 th sampling (14 days), it was noted that some immature neutrophils showed toxic granulations, similar to those described by Hine and Wain (1988). By the 6 th sampling (28 days), neutrophils showed an intense cytoplasmatic basophilia and in the 9 th week (49 days), monocytes showed numerous vacuoles and were comparatively larger than the monocytes in preceeding samplings.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Some changes were noticed in the morphology of leukocytes of O. niloticus during the course of the infection process. After the 4 th sampling (14 days), it was noted that some immature neutrophils showed toxic granulations, similar to those described by Hine and Wain (1988). By the 6 th sampling (28 days), neutrophils showed an intense cytoplasmatic basophilia and in the 9 th week (49 days), monocytes showed numerous vacuoles and were comparatively larger than the monocytes in preceeding samplings.…”
Section: Discussionsupporting
confidence: 81%
“…The increase in neutrophils represents a nonspecific immune response to the bacterial infection. Hine and Wain (1988) also observed in eels (Anguilla anguilla L.) injected with bacterial lipopolysaccarides the presence of neutrophils, these were intensively basophilic, more vacuolized and frequently found with an undifferentiated nucleus. According to Janini and Janini F o.…”
Section: Discussionmentioning
confidence: 80%
“…These results suggest that the increase in glycogen content of the inflammatory neutrophils observed in the inflamed peritoneal cavities of mammals (Scott & Cooper 1974, Robinson et al 1982 and fish (present results) would occur during the migration from the blood or in the inflammatory foci rather than in the haematopoietic tissues or peripheral blood. However, some reports described an increase in PAS staining of blood neutrophils of the eel (Nagamura & Wakabayashi 1985, Hine & Wain 1988 or rainbow trout (Lamas et al 1994) after the injection of bacteria or bacterial products. These conflicting results may well be explained by the use in the above studies of high doses of inflammatory agents which produced progressive disease and are likely to induce a systemic inflammatory reaction, therefore affecting circulating neutrophils.…”
Section: A B Cmentioning
confidence: 99%
“…It has been reported that inflammatory neutrophils of mammals (Scott & Cooper 1974, Robinson et al 1982 and the eel (Nagamura & Wakabayashi 1985, Hine & Wain 1988) contain more glycogen than resting neutrophils. This increase in the storage molecule would be useful for the metabolic activities of the neutrophils phagocytosing under the anaerobic conditions which frequently are faced by the phagocytes (Suzuki & Iida 1992).…”
Section: Introductionmentioning
confidence: 99%
“…When mono‐ or bi‐lobed granulocytes were encountered in coho salmon, they were smaller and the cytoplasm was basophilic. Hine & Wain (1988) also found basophilic granulocytes in short fin eels Anguilla australis Richardson injected with bacterial endotoxin and these often‐vacuolated cells with poorly defined nuclei were considered to be immature granulocytes. This suggests that the smaller basophilic cells found in juvenile coho salmon may have been precursors to polymorphonuclear adult cells.…”
Section: Discussionmentioning
confidence: 98%